2018
DOI: 10.1007/s12298-018-0600-x
|View full text |Cite
|
Sign up to set email alerts
|

An improved micropropagation and ex vitro rooting of a commercially important crop Henna (Lawsonia inermis L.)

Abstract: An improved micropropagation protocol has been developed for a cosmetically important, dye yielding crop, henna (Lawsonia inermis). Quality of henna product is governed by naphthoquinone based pigment lawsone, thus in vitro multiplication of superior healthy plant to achieve enhanced productivity in terms of dye content and biomass deserve due attention. In the present study, nodal explants collected from an elite plant screened on the basis of superiority in lawsone content was cultured on MS medium supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
3
0
2
Order By: Relevance
“…Henna (Lawsonia inermis L.) leaves are one of the main sources of natural hair dyes used in Asia and North Africa since antiquity, and are still extensively used today in a number of cosmetic applications including hair dyeing and skin painting. 1 The principal colouring agent in henna leaves is lawsone (2-hydroxy-1,4-naphthoquinone), also known as CI Natural Orange 6, which acts as a direct or mordant dye for hair fibre to give a red-orange colour. Besides hair dyeing, the interest in using henna for textile coloration has grown rapidly because of its green and ecofriendly nature.…”
Section: Introductionmentioning
confidence: 99%
“…Henna (Lawsonia inermis L.) leaves are one of the main sources of natural hair dyes used in Asia and North Africa since antiquity, and are still extensively used today in a number of cosmetic applications including hair dyeing and skin painting. 1 The principal colouring agent in henna leaves is lawsone (2-hydroxy-1,4-naphthoquinone), also known as CI Natural Orange 6, which acts as a direct or mordant dye for hair fibre to give a red-orange colour. Besides hair dyeing, the interest in using henna for textile coloration has grown rapidly because of its green and ecofriendly nature.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that 2.0 mg/L CPPU and 0.2 mg/L 2-ip can promote callus induction, and 3.0 mg/LCPPU can promote the growth of embryogenic callus in blueberry leaves ( Figure 1 and Figure 2 ; Table 9 and Table 10 ). In addition, CPPU [ 36 , 37 , 38 ] and 2iP [ 39 , 40 , 41 ] are active and promote bud growth in blueberries. In the present experiment, 1.0 mg/LCPPU and 0.4 mg/L 2-ip promote bud production and growth in blueberry, and the growth state of buds is better ( Figure 3 ; Table 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Los antecedentes de éxito de protocolos similares en otras especies herbáceas y en otras especies de la familia Lythraceae como lo es Lawsonia inermis, validan el empleo de citocininas para la producción de brotes y nuevas plántulas para la micropropagación de Heimia salicifolia, justificando así su adecuación a la especie del presente trabajo. Se han reportado, efectos positivos de la actividad de BA como la citocinina más activa para la multiplicación de explantes en plantas herbáceas, como Cassia angustifolia (Husain & Anis, 2009), Melia azadirachta (Ram & Shekhawat, 2011) y en Lawsonia inermis (Shiji & Siril, 2018); motivo por el cual se decidió su implementación en este protocolo, junto con el resto de los reguladores de crecimiento.…”
Section: Discussionunclassified
“…10). El tratamiento dos es eficaz para la producción de hojas y numerosos brotes vigorosos, lo cual se traduce en mayor cantidad de peso fresco producido, a emplearse en pruebas futuras referentes a su producción de alcaloides; estas concentraciones y su uso también ha sido eficaz en la micropropagación de otras especies con potencial farmacéutico, como Sophora tonkinensis (Jana et al, 2013) y en miembros de la misma familia como Lawsonia inermis (Shiji & Siril, 2018). La producción de hojas y brotes idénticas en los explantes basales contra los apicales del tratamiento dos, se relaciona con la disrupción de la dominancia apical del meristemo, proveyendo por lo tanto de un sistema eficaz y consistente para micropropagación de Heimia salicifolia sin muestra de signos de variación genética, generando una clonación a partir de dos vías de explantes, con lo cual se logra la duplicación de plántulas provenientes de una sola semilla germinada.…”
Section: Discussionunclassified